Influence of Supply Chain Management on Universities Development: An Outward Glance - Gabdrakhmanov, Niyaz K; Abilov, Albert V; Vershinina, Olga A; Novenkova, Aida Z; Medvedeva, Marina Yu (International Journal of Supply Chain Management, 2019)
This study is devoted to assessing the supply chain management impact on universities promotion and efficiency in international and Russian universities' ratings on their development. The peculiarity of the study is that it considers both universities participating in the competitive recovery program and presented in international rankings, as well as those that do not participate therein. The paper analyzes the rating indicators, the development strategy and the positioning of four Russian universities: Kazan (Volga Region) Federal University (KFU), National Research University "Higher School of Economics" (HSE), M.T. Kalashnikov Izhevsk State Technical University (IzhSTU) and G.R. Derzhavin Tambov State University (TSU). The research revealed the positive effects of the promotion in the university rankings on their development, among which the following can be distinguished: the formation of a competitive environment within the university, the definition of a specific strategic goal, the attraction of more qualified personnel to the university, including from the international academic market, etc. Negative consequences were revealed too, such as: increase in the workload on teachers, and as a result, reduced attention to the organization of the educational process, higher risk of losing the quality of scientific research, as a result of increasing the number of publications, ineffective spending of the university funds.